ANTIMICROBIAL ACTION OF COMPOSITIONS BASED ON SILVER NANOPARTICLES AND 3-HYDROXYPYRIDINE DERVATIVE - Gancho, O.V.; Loban, G.A.; Vazhnichaya, Ye.M.; Skripnik, N.V. (World of Medicine and Biology, 2014)
Among the promising tools in the market of new antimicrobial agents associated with nanotechnology one of the first position is occupied by nanoparticles (NPs) of silver, which have a wide range of antibacterial, antiviral and antiparasitic activity. According to current data regardless of the method of preparation, silver nanoparticles (NPs) have antibacterial and antifungal activity, the potency of which depends on the size, nature and condition of the surface coating. This effect is due to the release of silver ions and the formation of the interface defined between NPs and the cell. Nanosilver antimicrobial effects are more pronounced against gram-negative microflora and are propagating on biofilm- and spore forming strains, as well as on bacteria multi-resistant to antibiotics. As a result of studying the sensitivity museum strains of S. aureus ATCC 25923, S. epidermidis ATCC 14990, E. coli ATCC 25922, E. faecalis ATCC 29212, C. albicans ATCC 10231 to silver (Ag) nanoparticles obtained by electron-ray technology and dispersed in hydrophilic medium with the use of 3-hydroxypyridine derivative and polyvinylpyrrolidone (PVP) or dextran, it was shown that such dispersions exhibit antimicrobial activity against E. coli ATCC 25922. Among them liquid which is composed of Ag nanoparticles together with 3-hydroxypyridine derivative and PVP has the greatest bacteriostatic action. The aim of this study was to determine the antimicrobial properties of disperse systems based on various combinations of silver nanoparticles and condensate derivative 3- hydroxypyridine to the bacteria strains isolated from the oral cavity of healthy students. It is studied the sensitivity of strains isolated from oral cavity of students to silver nanoparticles (NPs) obtained by electron-beam technology and dispersed in hydrophilic medium with the use of 2-ethyl-6-methyl-3-hydroxypyridine succinate and polyvinyl pyrrolidone or dextran. Investigated the sensitivity of strains of microorganisms isolated from the oral fluid student volunteers to nanoparticles (NPs) of silver obtained by electron-beam technology, and dispersed in a hydrophilic medium with use of a 2-ethyl-6-methyl-3-hydroxypyridine succinate and polyvinyl pyrrolidone or dextran. It is shown that S. aureus, S. epidermidis, E. faecalis, Neisseria sp. and Bacillus sp. are sensitive to all studied samples of stabilized silver NPs. This sensitivity depends on the microorganism species, the nature of NPs coating and silver concentration. It indicates the prospects to use of silver NPs with different surface characteristics in dental diseases of infective-inflammatory genesis.